Cinco anos de melhoramento de algodão - Groszmann, Américo (Revista Ceres, 1943)
Cotton improvement in the Escola Superior de Agricultura of Minas Gerais in Viçosa, was begun in 1936 by Dr. J. B. Griffing in Viçosa, ex-president of the college. The author has continued this work after Mr. Griffing’s regress to the United States. Many cultural practices in relation with cotton, as date of planting, distances and fertilizers are already determined. There are 13 species of the genus Gossypium in the genetical colection and many hibrids of G. barbadense x G. hirsutum under studies to verily wilt resistance against Verticiium albo-atrum, and possible fiber improvement of G. hirsutum. A new coloration of the leaves was obtained by crossing Texas green lint. (red) and Virescent (yellow), which the author denominated «ferruginosa» (rust). From 100 g seeds of Acala introduced in 1937 this Department has distributed more than 4.000 quilos in 1942 and has plans to distribute 50.000 in 1943.